Integrating economic development and urban planning: Case study of Kansai, Japan, and PNWC, Western Australia - Martinus, Kirsten (The University of Western Australia, 2011)
Innovation and knowledge development are increasingly part of national productivity and economic development agendas. They are a product of a highly complex process embedded in human knowledge, experience and space. This has led many to argue that the key to future economic efficiency and sustainability lies in urban planning cognisant of human new economy needs. Such a hypothesis implies that some ‘places’ may be structurally more economically efficient than others. Therefore, understanding how urban form leverages social aspects of a city for economic growth offers a broad range of strategic and practical socio-economic applications. As part of a wider 4-year study exploring the capacity of hard infrastructure to influence the socio-economic imprint of urban space, this paper outlines the economic development and urban planning policies and strategies of Kansai, Japan and Perth’s North-West Corridor, Western Australia. Document analysis, site visits and interviews with key members of both region’s urban planning and economic development communities revealed two very different approaches to similar new economy socio-economic challenges. Urban development in Japan appears strongly focussed on economic development and the importance of fostering infrastructure supportive of human interaction and connectivity. Meanwhile, Western Australian strategies aim to increase effective land-use transport integration, and deliver more accessible and walkable catchments of daily living/working activities within otherwise strongly car-oriented communities.This paper summarises the effectiveness of respective approaches in delivering requirements for new economy efficiency, such as interaction and global network connectivity. It suggests that treating urban planning as an integral policy tool of economic development is likely to better address support national economic goals, such as increased innovation and knowledge development for productivity in the new economy.